2000
DOI: 10.4049/jimmunol.164.4.1761
|View full text |Cite
|
Sign up to set email alerts
|

Signals from the IL-9 Receptor Are Critical for the Early Stages of Human Intrathymic T Cell Development

Abstract: Highly purified human CD34+ hemopoietic precursor cells differentiate into mature T cells when seeded in vitro in isolated fetal thymic lobes of SCID mice followed by fetal thymus organ culture (FTOC). Here, this chimeric human-mouse FTOC was used to address the role of IL-9 and of the α-chain of the IL-9 receptor (IL-9Rα) in early human T cell development. We report that addition of the mAb AH9R7, which recognizes and blocks selectively the human high affinity α-chain of the IL-9R, results in a profound reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Although initially described as a T cell growth factor, naive T cells do not respond to IL-9, but recent data suggest that it is a critical factor for the early stages of intrathymic T cell maturation from precursor cells (12). It was also reported that IL-9 exerts growthenhancing activity on bone marrow-derived murine mast cell (BMMC) lines (13,14).…”
Section: Il-9 and Il-13 Production By Activated Mast Cells Is Stronglmentioning
confidence: 99%
“…Although initially described as a T cell growth factor, naive T cells do not respond to IL-9, but recent data suggest that it is a critical factor for the early stages of intrathymic T cell maturation from precursor cells (12). It was also reported that IL-9 exerts growthenhancing activity on bone marrow-derived murine mast cell (BMMC) lines (13,14).…”
Section: Il-9 and Il-13 Production By Activated Mast Cells Is Stronglmentioning
confidence: 99%
“…Thus, although we show that the IL-9R intracellular domain can mimic IL-7R in ␣␤ T cell development, the IL-9 pathway apparently is not operational in normal conditions, presumably for lack of ligand and/or receptor expression. There is a report that exogenously added IL-9 can promote human thymic development in vitro (29), which might suggest that the receptor is present but the ligand is unavailable. Whereas IL-7 is produced by thymic stromal cells, IL-9 is primarily produced by activated T cells that would make it generally unavailable to thymic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of IL-9 are mediated by the functional IL-9 receptor complex, that is composed of this protein as well as the IL-2 receptor gamma (IL-2RG), a common gamma subunit shared by the receptors of many different cytokines [7]. The activation of this receptor leads to the activation of various Janus kinases (JAK) and STAT proteins [8] which connect to different biological responses [6]. In GCA, IL-9R positivity was observed among endothelial cells of vessels distributed in the inflammatory infiltrates and neutrophils [20].…”
Section: Il-9 and Th9 Cells In Large-vessel Vasculitismentioning
confidence: 99%
“…IL-9 signals through a heterodimeric receptor composed by a specific IL-9 receptor chain (IL-9Ra) and the common g-chain (also known as IL2Rg) [8]. IL-9Ra is expressed on immune cells and its activation also promotes mast cell growth [8,9] and accumulation in inflamed tissues, innate lymphoid cells (ILC) survival and B cell immunoglobulin (Ig)E class-switch recombination [9][10][11] (Fig.…”
Section: Introductionmentioning
confidence: 99%